Exploring College Students’ English Language Learning Motivation and Their Teachers’ Motivational Strategies - ABBAS, SHEHAB A. R. (2023)
Motivation is a key element in the process of L2 learning. This leads many researchers to investigate the students' motivational factors, teachers' motivational strategies, students' perceptions about their teachers' strategies, and what strategies students use to maintain their L2 learning motivation insides and outside the classroom. The literature reveals that many studies explored students’ perceptions regarding their motivational factors for learning English but rarely tackled both students’ and teachers’ perceptions regarding students’ motivational components and the motivational strategies which teachers use to maintain or boost students’ English learning motivation. This study explores students' motivational factors and what approaches students use to maintain their motivation. Besides, it will explore EFL teachers’ and students’ views about motivational strategies used in Abu Dhabi EFL classrooms in order to investigate potential mismatches. Collecting qualitative and quantitative data adopted a mixed-method approach which was carried out in the academic context of three campuses in one of Abu-Dhabi's private colleges. This involved first the administration of a questionnaire to teachers and students. Second, six EFL teachers and six EFL students were in-depth interviewed individually for the purpose of exploring further those essential issues which might be revealed from both teachers and students' personal opinions in regard to motivational factors in learning the language along with those that might be shown in respect to teachers and students' viewpoint relating to the strategies adopted by teachers for motivating their students. Findings reveal that students have average interest and motivation to learn English. Besides, their motivation is mostly instrumental i.e., future career, academic study, and travelling. In addition, there are discrepancies between students and teachers’ perceptions of the important motivational strategies which should be used by teachers to boost students’ motivation to learn English. The findings will help teachers focus more on their students’ motivational factors; and consequently, they will help in tailoring their classes in a way which will be more motivating for the learners. Moreover, by having a clear picture of students’ perceptions of the motivational strategies used in classroom, teachers will have more awareness of the motivational strategies used in their classes. Moreover, policy makers of English language teaching in the UAE will get a good picture about how things go with college students regarding English language learning.